2019
DOI: 10.1088/1757-899x/662/3/032059
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Technology in Online Businesses College Students

Abstract: This study aims to providing an easy way for beginners in the business world to innovate in creating unique and interesting goods creation that can foster attractiveness for consumers and also create competitiveness in the business world. To support this research, a descriptive method was used by the interviewer. The results of the study found that the use of technology in online business is very helpful for students at Indonesian Computer University who run their online business. They use existing technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
0
0
1
Order By: Relevance
“…The results are similar to previous studies (Derguti & Shabani, 2015;Rahayu & Day 2017), which found that online businesses are able to increase sales among SME entrepreneurs, while Kurniawan & Gunawan (2019) found that online businesses can contribute to an increase in entrepreneurs' income. Source: Online survey (June 2020)…”
Section: Statements Regarding Online Businesssupporting
confidence: 91%
“…The results are similar to previous studies (Derguti & Shabani, 2015;Rahayu & Day 2017), which found that online businesses are able to increase sales among SME entrepreneurs, while Kurniawan & Gunawan (2019) found that online businesses can contribute to an increase in entrepreneurs' income. Source: Online survey (June 2020)…”
Section: Statements Regarding Online Businesssupporting
confidence: 91%
“…The service and responses amongst buyers and customers are quite fast while using latest technology in business; particularly students can maintain their online business successful along with their education by using technological facilities for online business such as the online shopping services, upstox, whatsapp, daraz, imo, cloud and zoom (Kurniawan, Gunawan, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Penggunaan teknologi meliputi penentuan tujuan, sasaran, dan fungsi dari teknologi itu sendiri untuk setiap orang atau organisasi. Salah satu bagian penting dalam menggunakan teknologi, khususnya bagi perusahaan, adalah membuat laporan keuangan yang baik [10]. Penelitian ini mendukung penelitian sebelumnya menurut [11], yang menyatakan bahwa laporan keuangan yang berkualitas dapat dihasilkan apabila sistem informasi akuntansi yang diterapkan terintegrasi dengan memanfaatkan teknologi.…”
unclassified